Blood Loss in Women of Childbearing Potential Taking Oral Anticoagulants for Venous Thromboembolism (The BLEED Study) - Grandone, Elvira; Mastroianno, Mario; Pacilli, Gabriella; Colaizzo, Donatella; Margaglione, Alessandra; Bikdeli, Behnood; Piazza, Gregory (Thrombosis and Haemostasis, 2024)
Oral anticoagulants (OAC) may exacerbate menstrual bleeding in women of childbearing age; however, the existing literature on this issue has several limitations.This study investigates abnormal uterine bleeding in women of childbearing age taking OAC–vitamin K antagonists or direct oral anticoagulants–for venous thromboembolism through a retrospective analysis of prospectively collected data. Uterine bleeding was assessed using the Pictorial Blood Assessment Chart (PBAC) and hemoglobin (Hb) values during anticoagulation compared with prior therapy. The number of unplanned medical visits for bleeding complications was also calculated.From June 2014 to November 2023, 110 women were recruited (median age, 36 years). PBAC scores correlated with Hb values at baseline and during therapy (analysis of variance [ANOVA], p < 0.01), with a significant difference in Hb values before and during anticoagulant therapy (delta Hb) among groups (ANOVA, p.0.034). Seventeen women (15.5%) reported uterine fibroids, experiencing a greater reduction in Hb values during anticoagulant administration than women without uterine fibroids (delta 0.3, interquartile range [IQR]: 0.8, 2.9 vs. 0.5, IQR 1.2, 0.3; p.0.012). Women with selfreported uterine fibroids required more frequent unplanned medical consultations for bleeding (mean visits 5 vs. 4, respectively; Poisson regression, p < 0.05). Among women with uterine fibroids, those taking apixaban showed smaller Hb changes than those on other oral anticoagulants (ANOVA, p.0.047). This difference persisted even after adjusting for potential confounders (multiple ANOVA, p.0.004).Women of childbearing age taking OAC frequently experience changes in Hb values and PBAC scores during treatment, with uterine fibroids playing a significant role.
Keywords: childbearing age; abnormal uterine bleeding; oral anticoagulants; uterine fibroids